Expression of c-erbB-2 oncogene product in Barrett's adenocarcinoma: pathological and prognostic correlations. Issue 1 (January 1994) - Fléjou, J F; Paraf, F; Muzeau, F; Fékété, F; Hénin, D; Jothy, S; Potet, F
Abstract : AIMS--To establish the prevalence of c-erbB-2 protein expression in a surgical series of Barrett's adenocarcinomas; and to correlate this expression with clinicopathological data and prognosis. METHODS--Sixty six surgical specimens of Barrett's adenocarcinomas were included in this retrospective study. Blocks of the tumour and of non-dysplastic Barrett's mucosa were stained with a polyclonal antibody specific for the intracytoplasmic domain of the c-erbB-2 protein. RESULTS--Seven of 66 tumours showed membrane staining for the c-erbB-2 protein. The non-dysplastic Barrett's mucosa was negative in all cases. There was no difference between c-erbB-2 positive and negative tumours with regard to mean age, sex ratio, percentage of alcohol misusers, percentage of smokers, tumour differentiation, depth of invasion, lymph node response, and proliferative activity, assessed by the percentage of tumour cells positive with the MIB-1 antibody directed against the Ki-67 antigen. All c-erb B2 positive tumours were of Lauren's intestinal type compared with negative c-erbB-2 tumours. Patients with c-erbB-2 positive tumours had a significantly poorer prognosis than patients with negative tumours. CONCLUSIONS--The prevalence of Barrett's adenocarcinomas expressing c-erbB-2 found in this study (11%) was similar to that observed in published series of gastric adenocarcinomas. c-erbB-2 protein expression could be an important prognostic indicator in Barrett's adenocarcinoma.